Can Painting Evoke the Kantian Sublime? - Clewis, Robert (Aesthetica Preprint, 2024)
Can painting evoke an experience of the sublime, understood in terms adopted by Kant in the Critique of the Power of Judgment? I will present three considerations that imply that painting cannot evoke the Kantian sublime. I then indicate some problems with each consideration. In the process, I explain how some paintings might evoke an experience of the sublime, even when painting is understood in terms of an eighteenth-century European context and conception of painting. In order to illustrate the phenomenology of sublime responses to paintings, I conclude with two examples. I thereby aim to show the real possibility of the Kantian sublime in response to painting.